PATIENT SAFETY CULTURE FROM THE NURSING TEAM’S PERSPECTIVE - Lopes, Brenda de Araújo; Cañedo, Mayara Carolina; Torres, Nívea Lorena; Lopes, Thiago Inácio Barros; Gaíva, Maria Aparecida Munhoz (Cogitare Enfermagem, 2023)
Objective: to identify the nursing staff knowledge about patient safety and the occurrence of adverse events in Emergency Medical Care. Method: cross-sectional, quantitative study, developed in a teaching hospital in the Midwest region of Brazil. It was conducted with nursing professionals through an online questionnaire containing questions related to patient safety, applied in September 2021. The data analysis was descriptive. Results: Ninety professionals participated in the study, 28(31.1%) being nurses and 62(68.9%) nursing technicians. In the evaluation of the questionnaire items, the best score was about hand hygiene 84(93.3%), the worst evaluated item was patient identification protocol 45(50%). Pressure ulcers were indicated as the most frequent adverse event 28(33%). Conclusion: the results indicate that continuing education is essential for professionals to apply the international patient safety goals in practice.